The HLA linked iron loading gene in an Afrikaner population. Issue 6 (June 1987) - Meyer, T E; Ballot, D; Bothwell, T H; Green, A; Derman, D P; Baynes, R D; Jenkins, T; Jooste, P L; du Toit, E D; Jacobs, P J
Abstract : The serum ferritin concentration was used as a screening test to identify the presence of iron overload in 599 Afrikaans subjects (300 males and 299 females) living in the South Western Cape, South Africa. Seventeen of the males with concentrations greater than 400 micrograms/l were reevaluated three and five years later. Serum ferritin concentrations were measured again and further diagnostic procedures were carried out. These included an assessment of alcohol intake and measurements of serum gamma glutamyltransferase, the percentage saturation of transferrin, and HLA-A, -B, -C, and -DR loci typing on the subjects as well as their families. Liver biopsies were performed on some affected subjects. Of the original 16 index subjects, four were diagnosed as homozygous for the HLA linked iron loading gene which is responsible for the clinical disease idiopathic haemochromatosis. Six appeared to be heterozygotes, three were heterozygotes who were also abusing alcohol, and two did not fit into any of the diagnostic groups. The calculated gene frequency was 0.082, with an expected heterozygote frequency of 0.148. The fact that no females were identified in the study suggested that the diagnostic criteria for homozygosity (serum ferritin greater than 400 micrograms/l and % saturation greater than 60%) were set too high. The data were therefore recalculated for the 300 males; when this was done the gene frequency was 0.115 and the heterozygote frequency 0.024. Two subjects were diagnosed as homozygotes in the study of family members and 37 as heterozygotes (33 definite and four probable). Both the homozygotes and nine of the heterozygotes showed mild to moderate disturbances of iron metabolism. There was considerable overlap between the phenotype expression in these nine heterozygotes and the homozygotes, probably as a result of setting the threshold for the serum ferritin concentrations at the relatively high value of 400 microgram/ml. By doing this a small subset of heterozygotes with biochemical abnormalities was identified. The results of the present pilot study suggest a high frequency of the HLA linked iron loading gene in the Afrikaner population of South Western Cape.